Industry Through Reinforcement of Institution and Human Power Resource - Nur, S; Djatmiko, OE; Zubaidah, S (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2000)
The failure of small scale animal farm industry development was indicated by the decreasing of animal farm number and the high price of their product. This failure has an effect into increasing of unemployment, decreasing of animal protein available and animal population because of the high rate of animal slaughtering and the high cost need to buy animal from other countries. This report was aimed to know the strategy on developing of stand alone small scale animal farm. This study based on literature study, panel discussion and interview. The result showed that the development of human power resource was the factor to decide the first priority in developing stand alone small scale animal farm. In the past the government policy always stussed in provision of capital for animal husbandry bussines developing, so it has never been the main priority. (Animal Production 2(2): 60-68 (2000)Â Key words : developing and reinforcement